STRATEGI GURU PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DALAM MENCEGAH PERILAKU BULLYING VERBAL DI SMA AL HUSNA KABUPATEN BOGOR - Elma Juita; Ade Wahidin; Ibrahim Bafadhol (Jurnal Manajemen Pendidikan, 2026)
Verbal bullying in schools is frequently normalized as mere teasing, despite its significant impact on adolescent mental health. This study aims to describe the forms of verbal bullying, analyze the preventive strategies of Islamic Religious Education (PAI) teachers, and identify supporting and inhibiting factors at SMA Al Husna, Bogor Regency. Utilizing a qualitative case study approach, data were gathered from PAI teachers, the principal, guidance counselors, and students through interviews, observation, and documentation. Data analysis applied the interactive model of Miles, Huberman, and Saldaña. The findings reveal that verbal bullying includes mocking parents' names, calling peers animal names, harsh language, and insults. The PAI teachers' preventive strategies encompass integrating speech-guarding values into learning, modeling polite language, employing persuasive family-like approaches, conducting religious habits, and collaborating with guidance counselors. Supporting factors include the school’s religious culture and regulations. However, implementation is hindered by negative social media influences, the normalization of harsh language among adolescents, and victims' reluctance to report incidents. Comprehensive prevention requires continuous synergy among all school members to cultivate a safe, character-driven educational environment